Brazing method for ZrB2-SiC-C ceramic composite material and nickel-based superalloy
By using Cu-Ti brazing material and Nb foil intermediate layer in the brazing connection between ZrB2-SiC-C ceramic composite and nickel-based high-temperature alloy, the problems of brazing wetting difficulties, Ni element dissolution and linear expansion coefficient mismatch were solved, and high-strength and low-stress joints were achieved.
Patent Information
- Application Number
- CN202411904105.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-23
AI Technical Summary
In the brazing connection between ZrB2-SiC-C ceramic composite material and nickel-based high-temperature alloy, there are problems such as brazing material wetting on the ceramic composite material, dissolution of Ni elements in nickel-based high-temperature alloy resulting in the formation of brittle compounds, and mismatch of linear expansion coefficients resulting in excessive residual stress.
Cu-Ti solder is used and Nb foil is added to the intermediate layer, wetting is achieved by reacting Ti with ZrB2-SiC-C ceramic composite material, and diffusion of Ni is prevented and stress relief is relieved through Nb foil. At the same time, ZrB2-SiC-C ceramic composite mesh structure is introduced into the joint to form a gradient transition of the thermal expansion coefficient.
It effectively solves the wetting problem of solder and ceramic composite materials, reduces the formation of brittle compounds, relieves residual stress in the joint, and improves the shear strength of the joint.
Smart Images

Figure CN119634866A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a brazing method for a ceramic composite material and a nickel-based high-temperature alloy. Background Art
[0002] Ultra-high temperature ceramic composites can serve in ultra-high temperatures and harsh environments due to their stable properties. Typical ultra-high temperature ceramic composites include ZrB2-SiC, HfB2-SiC, ZrB2-SiC-C, etc. Compared with other ceramic composites, ZrB2-SiC-C ceramic composites have a higher melting point, higher Young's modulus, higher hardness, better electrical and thermal conductivity, and chemical corrosion resistance, making them more widely used in ultra-high temperature structural functional materials with harsh service conditions, such as high-speed aircraft wing rudders and engine nozzles in the aerospace field. The excellent performance of ZrB2-SiC-C ceramic composites is due to its constituent components. ZrB2 has a high melting point and good chemical stability, can maintain high strength at high temperatures, and has relatively good thermal shock resistance and oxidation resistance; the addition of SiC can effectively increase the high temperature strength and fracture toughness of ceramic composites, and greatly improve the oxidation resistance of the material; adding a certain amount of C can greatly increase the thermal conductivity of the material, thereby improving the thermal shock resistance of the material. However, the manufacture of large-sized components still requires the connection of ZrB2-SiC-C ceramic composites and metals. Nickel-based superalloys are widely used in high-temperature components in the aerospace field such as jet engines due to their high strength and good oxidation resistance. Therefore, the reliable connection of two important high-temperature materials, ZrB2-SiC-C ceramic composites and nickel-based superalloys, to obtain joints with excellent mechanical properties has broad application prospects.
[0003] The connection between ultra-high temperature ceramic composites and high temperature alloys is usually made by brazing. There are three main difficulties in the brazing connection between ZrB2-SiC-C ceramic composites and nickel-based high temperature alloys: (1) ZrB2-SiC-C ceramic composites are composed of three phases: ZrB2, SiC, and graphite. For brazing, it is necessary to ensure that the brazing material can achieve good wetting of the three phases at the same time. (2) Nickel-based high temperature alloys are easily dissolved in the brazing material, resulting in a large amount of Ni in the weld. Ni is an active element, and the reaction between Ni and Si can easily lead to the intergranular penetration of the weld metal into the ZrB2-SiC-C ceramic composite, forming a brittle weak area within a certain range on the surface of the parent material; (3) The linear expansion coefficient of the ZrB2-SiC-C ceramic composite is between 7.5×10 -6 / ℃, while the linear expansion coefficient of nickel-based high-temperature alloys is 16-18×10 -6 / ℃, the difference between the two is large, which will cause large residual stress in the joint during the cooling process, weakening the joint performance. Summary of the invention
[0004] In order to solve the three problems of difficulty in wetting the ZrB2-SiC-C ceramic composite material base material by the brazing filler metal, the dissolution of Ni element in the nickel-based high-temperature alloy into the brazing filler metal to generate a large amount of brittle compounds at the side interface of the ZrB2-SiC-C ceramic composite material, and the mismatch of linear expansion coefficients between the ZrB2-SiC-C ceramic composite material and the nickel-based high-temperature alloy, the present invention proposes a brazing method for ZrB2-SiC-C ceramic composite material and nickel-based high-temperature alloy. The present invention adopts Cu-Ti brazing filler metal to braze the ZrB2-SiC-C ceramic composite material and the nickel-based high-temperature alloy, and utilizes Ti in the Cu-Ti brazing filler metal as an active element to react with the ZrB2-SiC-C ceramic composite material, thereby achieving wetting of the ceramic composite material base material by the brazing filler metal, and by adding Nb foil as a composite intermediate layer in the Cu-Ti brazing filler metal, it plays a role in blocking Ni diffusion and relieving joint stress. On the basis of adding the Nb foil intermediate layer, the ZSC (ZrB2-SiC-C ceramic composite material) mesh structure is added to further promote the gradient transition of the thermal expansion coefficient of the ZSC ceramic composite material to the nickel-based high-temperature alloy, which plays a role in relieving the joint stress and hindering the crack propagation, and realizes the reliable connection of the ZSC ceramic composite material and the nickel-based high-temperature alloy.
[0005] The brazing method of the ZrB2-SiC-C ceramic composite material and the nickel-based high-temperature alloy of the present invention is carried out according to the following steps:
[0006] 1. Grinding and cleaning of ZrB2-SiC-C ceramic composite materials before welding;
[0007] The pre-welding grinding and cleaning treatment method comprises: grinding the surface to be welded of the ZrB2-SiC-C ceramic composite material step by step, and then placing it in a cleaning agent for ultrasonic cleaning for 5-60 minutes; and placing the cleaned ZrB2-SiC-C ceramic composite material in anhydrous ethanol or acetone for liquid sealing for standby use;
[0008] The cleaning agent is anhydrous ethanol or acetone;
[0009] 2. Grind and clean the nickel-based high-temperature alloy before welding;
[0010] The pre-welding grinding and cleaning treatment method is as follows: grinding the surface to be welded of the nickel-based high-temperature alloy step by step, and then placing it in a cleaning agent for ultrasonic cleaning for 5-60 minutes;
[0011] The cleaning agent is anhydrous ethanol or acetone;
[0012] 3. preparing a Cu-Ti solder; the mass fraction of TiH2 in the Cu-Ti solder is 10%-40%;
[0013] The preparation method of the Cu-Ti solder is as follows: weighing Cu powder and TiH2 powder, and then grinding them evenly to obtain the Cu-Ti solder;
[0014] 4. Grinding and cleaning the Nb foil before welding; the thickness of the Nb foil is 50-200 μm;
[0015] The pre-welding grinding and cleaning treatment method is: grinding the two surfaces of the Nb foil step by step, placing it in a cleaning agent for ultrasonic cleaning for 5-60 minutes after grinding, and finally cleaning it with a solvent; the cleaning agent is anhydrous ethanol or acetone; the solvent is anhydrous ethanol or acetone;
[0016] 5. Assembly of welded parts: stack and fix the ZrB2-SiC-C ceramic composite material, Cu-Ti brazing filler metal, Nb foil, Cu-Ti brazing filler metal, and nickel-based high-temperature alloy in this order to obtain the welded parts;
[0017] 6. Put the parts to be welded into the vacuum brazing furnace for vacuum brazing.
[0018] The vacuum brazing process is as follows: under vacuum conditions, heating to 910°C-990°C at a heating rate not exceeding 15°C / min and keeping the temperature for 1-40min, and then cooling to room temperature at a cooling rate not exceeding 10°C / min.
[0019] Another brazing method of a ZrB2-SiC-C ceramic composite material and a nickel-based high-temperature alloy of the present invention is carried out according to the following steps:
[0020] 1. Grinding and cleaning of ZrB2-SiC-C ceramic composite materials before welding;
[0021] The pre-welding grinding and cleaning treatment method comprises: grinding the surface to be welded of the ZrB2-SiC-C ceramic composite material step by step, and then placing it in a cleaning agent for ultrasonic cleaning for 5-60 minutes after grinding;
[0022] The cleaning agent is anhydrous ethanol or acetone;
[0023] 2. Grind and clean the nickel-based high-temperature alloy before welding;
[0024] The pre-welding grinding and cleaning treatment method comprises: grinding the surface of the nickel-based high-temperature alloy to be welded step by step, and then placing the surface in a cleaning agent for ultrasonic cleaning for 5-60 minutes; and placing the cleaned nickel-based high-temperature alloy in anhydrous ethanol or acetone for liquid sealing for standby use;
[0025] The cleaning agent is anhydrous ethanol or acetone;
[0026] 3. preparing a Cu-Ti solder; the mass fraction of TiH2 in the Cu-Ti solder is 10%-40%;
[0027] The preparation method of the Cu-Ti solder is as follows: weighing Cu powder and TiH2 powder, and then grinding them evenly to obtain the Cu-Ti solder;
[0028] 4. Grinding and cleaning the Nb foil and ZrB2-SiC-C ceramic composite mesh before welding;
[0029] The thickness of the Nb foil is 50-200 μm;
[0030] The preparation method of the ZrB2-SiC-C ceramic composite material net is as follows: the ZrB2-SiC-C ceramic composite material is cut into thin slices with a thickness of 0.2-1 mm by wire cutting, and a hole with a diameter of 0.2-1 mm is processed on the thin slice by a pulse laser to obtain the ZrB2-SiC-C ceramic composite material net; the porosity of the ZrB2-SiC-C ceramic composite material net is 5%-30%;
[0031] The pre-welding grinding and cleaning treatment method is: grinding the two surfaces of the Nb foil step by step, placing it in a cleaning agent for ultrasonic cleaning for 5-60 minutes after grinding, and finally cleaning it with a solvent; the cleaning agent is anhydrous ethanol or acetone; the solvent is anhydrous ethanol or acetone;
[0032] 5. Assembly of welded parts: stack and fix the ZrB2-SiC-C ceramic composite material, Cu-Ti brazing filler metal, ZrB2-SiC-C ceramic composite material mesh, Cu-Ti brazing filler metal, Nb foil, Cu-Ti brazing filler metal, and nickel-based high-temperature alloy in this order to obtain the welded parts;
[0033] 6. Put the parts to be welded into the vacuum brazing furnace for vacuum brazing.
[0034] The vacuum brazing process is as follows: under vacuum conditions, heating to 910°C-990°C at a heating rate not exceeding 15°C / min and keeping the temperature for 1-40min, and then cooling to room temperature at a cooling rate not exceeding 10°C / min.
[0035] The principles and beneficial effects of the present invention are:
[0036] In the present invention, the brazing of the ZrB2-SiC-C ceramic composite material and the nickel-based high-temperature alloy adopts a Nb foil intermediate layer, so that the brazing seam structure of the ZrB2-SiC-C ceramic composite material side is mainly composed of Cu(s,s) and Cu-Ti compound phases, which effectively blocks the dissolution of Ni in the nickel-based high-temperature alloy into the brazing material on the ZrB2-SiC-C ceramic composite material side, solves the problem that Ni consumes the activity of the active element Ti in the brazing material, avoids the reaction of Ni and Si to produce weld metal and the intergranular penetration of the ZrB2-SiC-C ceramic composite material, and also improves the brazing seam structure and reduces the generation of brittle compounds on the side of the ZrB2-SiC-C ceramic composite material. In addition, the linear expansion coefficient of Nb is 8.5-12.3×10 -6 / ℃, which is between the ZrB2-SiC-C ceramic composite material and the nickel-based high-temperature alloy, plays the role of linear expansion coefficient transition, thereby alleviating the residual stress of the joint.
[0037] The brazing of the ZrB2-SiC-C ceramic composite material and the nickel-based high-temperature alloy of the present invention adopts a ZrB2-SiC-C ceramic composite material mesh structure, which is conducive to forming a gradient transition of the thermal expansion coefficient from the ZSC ceramic composite material to the nickel-based high-temperature alloy, further relieving the joint stress, and also absorbing a part of the fracture work. In addition, when the crack expands in the middle layer of the ZrB2-SiC-C ceramic composite material mesh, it needs to pass through the brazing filler metal infiltrated in the pores of the ceramic composite material, and the crack expansion in the metal consumes more energy than the expansion inside the ceramic composite material. Therefore, the brazing filler metal in the mesh of the ZrB2-SiC-C ceramic composite material mesh will have a certain hindering effect on the expansion of the crack, further improving the shear strength of the joint. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is a picture of the interface structure of the brazed joint obtained in Example 1;
[0039] Figure 2 This is a picture of the joint interface structure obtained in Example 2;
[0040] Figure 3 This is the fracture morphology of the joint obtained in Example 2;
[0041] Figure 4 This is an elemental surface scanning image of Ni, Ti, and Cu in the joint obtained in Comparative Example 1. DETAILED DESCRIPTION
[0042] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any reasonable combination of the specific implementation modes.
[0043] Specific implementation method 1: The brazing method of the ZrB2-SiC-C ceramic composite material and the nickel-based high-temperature alloy in this implementation method is carried out according to the following steps:
[0044] 1. Grinding and cleaning of ZrB2-SiC-C ceramic composite materials before welding;
[0045] 2. Grind and clean the nickel-based high-temperature alloy before welding;
[0046] 3. preparing a Cu-Ti solder; the mass fraction of TiH2 in the Cu-Ti solder is 10%-40%;
[0047] 4. Grinding and cleaning the Nb foil before welding; the thickness of the Nb foil is 50-200 μm;
[0048] 5. Assembly of welded parts: stack and fix the ZrB2-SiC-C ceramic composite material, Cu-Ti brazing filler metal, Nb foil, Cu-Ti brazing filler metal, and nickel-based high-temperature alloy in this order to obtain the welded parts;
[0049] 6. Put the parts to be welded into the vacuum brazing furnace for vacuum brazing.
[0050] The vacuum brazing process is as follows: under vacuum conditions, heating to 910°C-990°C at a heating rate not exceeding 15°C / min and keeping the temperature for 1-40min, and then cooling to room temperature at a cooling rate of 10°C / min.
[0051] In this embodiment, the brazing of ZrB2-SiC-C ceramic composite material and nickel-based high-temperature alloy adopts Nb foil intermediate layer, so that the brazing seam structure of ZrB2-SiC-C ceramic composite material side is mainly composed of Cu(s,s) and Cu-Ti compound phases, which effectively blocks the dissolution of Ni in nickel-based high-temperature alloy into the brazing material on the ZrB2-SiC-C ceramic composite material side, solves the problem of Ni consuming the activity of active element Ti in the brazing material, avoids the reaction of Ni and Si to produce weld metal and the intergranular penetration of ZrB2-SiC-C ceramic composite material, and also improves the brazing seam structure and reduces the generation of brittle compounds on the side of ZrB2-SiC-C ceramic composite material. In addition, the linear expansion coefficient of Nb is 8.5-12.3×10 -6 / ℃, which is between the ZrB2-SiC-C ceramic composite material and the nickel-based high-temperature alloy, plays the role of linear expansion coefficient transition, thereby alleviating the residual stress of the joint.
[0052] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that: the pre-welding grinding and cleaning treatment method described in step 1 is: the surface to be welded of the ZrB2-SiC-C ceramic composite material is ground step by step, and after grinding, it is placed in a cleaning agent for ultrasonic cleaning for 5-60 minutes; the cleaned ZrB2-SiC-C ceramic composite material is placed in anhydrous ethanol or acetone for liquid sealing for standby use; the cleaning agent is anhydrous ethanol or acetone.
[0053] Specific implementation method three: This implementation method is different from specific implementation methods one or two in that: the pre-welding grinding and cleaning treatment method described in step two is: the surface to be welded of the nickel-based high-temperature alloy is ground step by step, and after grinding, it is placed in a cleaning agent for ultrasonic cleaning for 5-60 minutes; the cleaning agent is anhydrous ethanol or acetone.
[0054] Specific implementation method 4: This implementation method is different from any one of specific implementation methods 1 to 3 in that: the preparation method of the Cu-Ti solder described in step 3 is: weighing Cu powder and TiH2 powder, and then grinding them evenly to obtain Cu-Ti solder.
[0055] Specific implementation method five: This implementation method is different from any one of specific implementation methods one to four in that: the pre-welding grinding and cleaning treatment method described in step four is: the two surfaces of the Nb foil are ground step by step, and after grinding, they are placed in a cleaning agent for ultrasonic cleaning for 5-60 minutes, and finally cleaned with a solvent; the cleaning agent is anhydrous ethanol or acetone; the solvent is anhydrous ethanol or acetone.
[0056] Specific embodiment 6: The brazing method of the ZrB2-SiC-C ceramic composite material and the nickel-based high-temperature alloy in this embodiment is carried out according to the following steps:
[0057] 1. Grinding and cleaning of ZrB2-SiC-C ceramic composite materials before welding;
[0058] 2. Grind and clean the nickel-based high-temperature alloy before welding;
[0059] 3. preparing a Cu-Ti solder; the mass fraction of TiH2 in the Cu-Ti solder is 10%-40%;
[0060] 4. Grinding and cleaning the Nb foil and the ZrB2-SiC-C ceramic composite material mesh before welding; the thickness of the Nb foil is 50-200 μm;
[0061] The preparation method of the ZrB2-SiC-C ceramic composite material net is as follows: the ZrB2-SiC-C ceramic composite material is cut into thin slices with a thickness of 0.2-1 mm by wire cutting, and a hole with a diameter of 0.2-1 mm is processed on the thin slice by a pulse laser to obtain the ZrB2-SiC-C ceramic composite material net; the porosity of the ZrB2-SiC-C ceramic composite material net is 5%-30%;
[0062] 5. Assembly of welded parts: stack and fix the ZrB2-SiC-C ceramic composite material, Cu-Ti brazing filler metal, ZrB2-SiC-C ceramic composite material mesh, Cu-Ti brazing filler metal, Nb foil, Cu-Ti brazing filler metal, and nickel-based high-temperature alloy in this order to obtain the welded parts;
[0063] 6. Put the parts to be welded into the vacuum brazing furnace for vacuum brazing.
[0064] The vacuum brazing process is: under vacuum conditions, the temperature is raised to 910°C-990°C at a heating rate not exceeding 15°C / min and kept for 1-40 minutes, and then cooled to room temperature at a cooling rate not exceeding 10°C / min. In this embodiment, the brazing of ZrB2-SiC-C ceramic composite material and nickel-based high-temperature alloy adopts a Nb foil intermediate layer, so that the brazing seam structure of the ZrB2-SiC-C ceramic composite material side is mainly composed of Cu(s,s) and Cu-Ti compound phases, which effectively blocks the dissolution of Ni in the nickel-based high-temperature alloy into the brazing material on the side of the ZrB2-SiC-C ceramic composite material, solves the problem of Ni consuming the activity of the active element Ti in the brazing material, avoids the reaction of Ni and Si to produce weld metal and the intergranular penetration of ZrB2-SiC-C ceramic composite material, and also improves the brazing seam structure and reduces the generation of brittle compounds on the side of the ZrB2-SiC-C ceramic composite material. In addition, the linear expansion coefficient of Nb is 8.5-12.3×10 -6 / ℃, which is between the ZrB2-SiC-C ceramic composite material and the nickel-based high-temperature alloy, plays the role of linear expansion coefficient transition, thereby alleviating the residual stress of the joint.
[0065] In this embodiment, the brazing of ZrB2-SiC-C ceramic composite material and nickel-based high temperature alloy adopts ZrB2-SiC-C ceramic composite material mesh structure, which is conducive to forming a gradient transition of thermal expansion coefficient from ZSC ceramic composite material to nickel-based high temperature alloy, further relieving joint stress, and also absorbing part of the fracture work. In addition, when the crack expands in the middle layer of ZrB2-SiC-C ceramic composite material mesh, it needs to pass through the brazing filler metal infiltrated in the pores of the ceramic composite material, and the crack expansion in the metal consumes more energy than the expansion inside the ceramic composite material. Therefore, the brazing filler metal in the mesh of ZrB2-SiC-C ceramic composite material mesh will play a certain role in hindering the expansion of the crack, further improving the shear strength of the joint.
[0066] Specific implementation method seven: This implementation method is different from specific implementation method six in that: the pre-welding grinding and cleaning treatment method described in step one is: the surface to be welded of the ZrB2-SiC-C ceramic composite material is ground step by step, and after grinding, it is placed in a cleaning agent for ultrasonic cleaning for 5-60 minutes; the cleaning agent is anhydrous ethanol or acetone.
[0067] Specific implementation eight: This implementation differs from specific implementation six or seven in that: the pre-welding grinding and cleaning method described in step two is: grinding the surface of the nickel-based high-temperature alloy to be welded step by step, and placing it in a cleaning agent for ultrasonic cleaning for 5-60 minutes after grinding; the cleaned nickel-based high-temperature alloy is placed in anhydrous ethanol or acetone for liquid sealing for standby use; the cleaning agent is anhydrous ethanol or acetone.
[0068] Specific embodiment nine: This embodiment differs from any one of specific embodiments six to eight in that: the preparation method of the Cu-Ti solder described in step three is: weighing Cu powder and TiH2 powder, and then grinding them evenly to obtain the Cu-Ti solder.
[0069] Specific embodiment ten: This embodiment differs from any one of specific embodiments six to nine in that: the pre-welding grinding and cleaning treatment method described in step four is: grinding the two surfaces of the Nb foil step by step, placing it in a cleaning agent for ultrasonic cleaning for 5-60 minutes after grinding, and finally cleaning it with a solvent; the cleaning agent is anhydrous ethanol or acetone; the solvent is anhydrous ethanol or acetone.
[0070] Example 1
[0071] The brazing method of the ZrB2-SiC-C ceramic composite material and the nickel-based high-temperature alloy in this embodiment is carried out according to the following steps:
[0072] 1. Grinding and cleaning of ZrB2-SiC-C ceramic composite materials before welding;
[0073] The pre-welding grinding and cleaning treatment method comprises: cutting the ZrB2-SiC-C ceramic composite material into test pieces of 4mm×4mm×3mm in size, grinding the surface to be welded of the ZrB2-SiC-C ceramic composite material step by step with 400 mesh, 800 mesh, 1500 mesh and 2000 mesh diamond sandpaper, and ultrasonically cleaning the surface in a cleaning agent for 15 minutes after grinding; and placing the cleaned ZrB2-SiC-C ceramic composite material in anhydrous ethanol for liquid sealing for standby use;
[0074] The cleaning agent is anhydrous ethanol;
[0075] 2. Grind and clean the nickel-based high-temperature alloy before welding;
[0076] The pre-welding grinding and cleaning treatment method is as follows: the nickel-based high-temperature alloy is cut into test pieces of 20 mm×10 mm×2 mm in size, the surface to be welded of the nickel-based high-temperature alloy is ground step by step using 400 mesh and 800 mesh diamond sandpaper, and after grinding, the nickel-based high-temperature alloy is ultrasonically cleaned in a cleaning agent for 15 minutes; the cleaned nickel-based high-temperature alloy is placed in anhydrous ethanol for liquid sealing for standby use;
[0077] The cleaning agent is anhydrous ethanol;
[0078] The nickel-based high-temperature alloy is GH99 high-temperature alloy;
[0079] 3. preparing a Cu-Ti solder, wherein the mass fraction of TiH2 in the Cu-Ti solder is 25%;
[0080] The preparation method of the Cu-Ti solder is as follows: weighing Cu powder and TiH2 powder, and then grinding them evenly to obtain the Cu-Ti solder;
[0081] 4. Grinding and cleaning the Nb foil before welding; the thickness of the Nb foil is 80 μm;
[0082] The pre-welding grinding and cleaning treatment method is: the two surfaces of the Nb foil are sequentially ground with 400 mesh, 800 mesh, 1500 mesh, and 2000 mesh diamond sandpaper, and after grinding, they are ultrasonically cleaned in a cleaning agent for 15 minutes, and finally cleaned with a solvent; the cleaning agent is anhydrous ethanol; the solvent is anhydrous ethanol;
[0083] 5. Assembly of welded parts: stack and fix the ZrB2-SiC-C ceramic composite material, Cu-Ti brazing filler metal, Nb foil, Cu-Ti brazing filler metal, and nickel-based high-temperature alloy in this order to obtain the welded parts;
[0084] 6. Put the parts to be welded into the vacuum brazing furnace for vacuum brazing.
[0085] The vacuum brazing process is as follows: under vacuum conditions, the temperature is raised to 950° C. at a heating rate of 15° C. / min and kept at that temperature for 10 minutes, and then the temperature is lowered to room temperature at a cooling rate of 5° C. / min.
[0086] The shear test was carried out using an electronic universal testing machine with a loading speed of 0.5 mm / min. The room temperature shear strength of the connection joint obtained in Example 1 reached 85 MPa. Figure 1 The interface structure picture of the brazed joint obtained in Example 1 includes the enlarged pictures of the A, B, and D areas in the brazed joint; Figure 1 The results show that the joint is well connected. Combined with the energy spectrum analysis, it is found that the reaction products on the ZSC ceramic composite side of the joint are Ti-Si, Ti-Si-C, Ti-C, and Ti-Cu compounds, indicating that the Nb foil intermediate layer blocks the effect of the dissolution of Ni in GH99 on the brazing seam on the ZSC ceramic composite side. The brazing seam structure on the ZSC ceramic composite side is mainly formed by Cu(s,s) and Cu-Ti compound phases, and no brittle Ti-Ni compounds appear, thereby ensuring the activity of the active element Ti in the brazing filler metal, while also improving the brazing seam structure and reducing the amount of brittle compounds on the ZSC parent material side. In addition, the linear expansion coefficient of Nb is between that of the ZSC ceramic composite and the GH99 nickel-based high-temperature alloy, which plays a role in the transition of the linear expansion coefficient, thereby alleviating the residual stress of the joint.
[0087] Table 1 Energy spectrum analysis data at the joint interface (at.%)
[0088]
[0089]
[0090] Example 2
[0091] The brazing method of the ZrB2-SiC-C ceramic composite material and the nickel-based high-temperature alloy in this embodiment is carried out according to the following steps:
[0092] 1. Grinding and cleaning of ZrB2-SiC-C ceramic composite materials before welding;
[0093] The pre-welding grinding and cleaning treatment method comprises: cutting the ZrB2-SiC-C ceramic composite material into test pieces of 4mm×4mm×3mm in size, grinding the surface to be welded of the ZrB2-SiC-C ceramic composite material step by step with 400 mesh, 800 mesh, 1500 mesh and 2000 mesh diamond sandpaper, and ultrasonically cleaning the surface in a cleaning agent for 15 minutes after grinding; and placing the cleaned ZrB2-SiC-C ceramic composite material in anhydrous ethanol for liquid sealing for standby use;
[0094] The cleaning agent is anhydrous ethanol;
[0095] 2. Grind and clean the nickel-based high-temperature alloy before welding;
[0096] The pre-welding grinding and cleaning treatment method is as follows: the nickel-based high-temperature alloy is cut into test pieces of 20 mm×10 mm×2 mm in size, the surface to be welded of the nickel-based high-temperature alloy is ground step by step using 400 mesh and 800 mesh diamond sandpaper, and after grinding, the nickel-based high-temperature alloy is ultrasonically cleaned in a cleaning agent for 15 minutes; the cleaned nickel-based high-temperature alloy is placed in anhydrous ethanol for liquid sealing for standby use;
[0097] The cleaning agent is anhydrous ethanol;
[0098] The nickel-based high-temperature alloy is GH99 high-temperature alloy;
[0099] 3. preparing a Cu-Ti solder, wherein the mass fraction of TiH2 in the Cu-Ti solder is 25%;
[0100] The preparation method of the Cu-Ti solder is as follows: weighing Cu powder and TiH2 powder, and then grinding them evenly to obtain the Cu-Ti solder;
[0101] 4. Grinding and cleaning the Nb foil and ZrB2-SiC-C ceramic composite mesh before welding;
[0102] The pre-welding grinding and cleaning treatment method is: the two surfaces of the Nb foil are sequentially ground with 400 mesh, 800 mesh, 1500 mesh, and 2000 mesh diamond sandpaper, and after grinding, they are ultrasonically cleaned in a cleaning agent for 15 minutes, and finally cleaned with a solvent; the cleaning agent is anhydrous ethanol; the solvent is anhydrous ethanol;
[0103] The thickness of the Nb foil is 50-200 μm;
[0104] The preparation method of the ZrB2-SiC-C ceramic composite material net is as follows: the ZrB2-SiC-C ceramic composite material is cut into a thin slice with a thickness of 0.5 mm by wire cutting, and a hole with a diameter of 0.5 mm is processed on the thin slice by a pulse laser to obtain the ZrB2-SiC-C ceramic composite material net; the porosity of the ZrB2-SiC-C ceramic composite material net is 11%, the holes are arranged in a square array, and the interval between the holes is 1 mm;
[0105] 5. Assembly of welded parts: stack and fix the ZrB2-SiC-C ceramic composite material, Cu-Ti brazing filler metal, ZrB2-SiC-C ceramic composite material mesh, Cu-Ti brazing filler metal, Nb foil, Cu-Ti brazing filler metal, and nickel-based high-temperature alloy in this order to obtain the welded parts;
[0106] 6. Put the parts to be welded into the vacuum brazing furnace for vacuum brazing.
[0107] The vacuum brazing process is as follows: under vacuum conditions, heating to 450°C at a heating rate of 15°C / min and keeping warm for 30 minutes, then heating to 750°C at a heating rate of 10°C / min and keeping warm for 20 minutes, then heating to 950°C at a heating rate not exceeding 5°C / min and keeping warm for 10 minutes, and then cooling to room temperature at a cooling rate of 5°C / min.
[0108] The shear test was carried out using an electronic universal testing machine with a loading speed of 0.5 mm / min. The room temperature shear strength of the connection joint obtained in Example 2 reached 107 MPa. Figure 2 Joint interface analysis, Figure 3 The fracture analysis shows that the joint breaks inside the ZSC ceramic composite material and the ZSC mesh middle layer, which means that under the action of external force, the crack initiates in the ZSC mesh middle layer and then expands into the ZSC ceramic composite material. The crack path deflects during the expansion process and absorbs part of the fracture work. In addition, when the crack expands in the ZSC mesh middle layer, it needs to pass through the brazing metal infiltrated in the pores of the ceramic composite material. The crack expansion in the metal consumes more energy than the expansion inside the ceramic composite material. Therefore, the brazing metal in the pores of the ceramic composite material will hinder the expansion of the crack. The ZrB2-SiC-C ceramic composite mesh further improves the strength of the joint.
[0109] Comparative Example 1
[0110] The brazing method of the ZSC ceramic composite material and the nickel-based high-temperature alloy in this comparative example is carried out according to the following steps:
[0111] 1. Pre-welding treatment of ZSC ceramic composite materials (ZrB2-SiC-C ceramic composite materials):
[0112] The ZSC ceramic composite material was cut into specimens of 4 mm × 4 mm × 3 mm by wire cutting, and the surface of the ZSC ceramic composite material was polished step by step with 400 mesh, 800 mesh, 1500 mesh, and 2000 mesh diamond sandpaper, and the treated ZSC ceramic composite material was ultrasonically cleaned in a cleaning agent for 15 minutes. The cleaned ZSC ceramic composite material was placed in anhydrous ethanol and sealed for standby use.
[0113] 2. Pre-welding treatment of nickel-based high-temperature alloys:
[0114] The GH99 high-temperature alloy was cut into specimens of 20 mm × 10 mm × 2 mm in size. The surface of the GH99 high-temperature alloy was polished step by step with 400 mesh and 800 mesh diamond sandpaper, and the treated GH99 high-temperature alloy was ultrasonically cleaned in a cleaning agent for 15 minutes. The cleaned nickel-based high-temperature alloy was placed in anhydrous ethanol for liquid sealing and standby use.
[0115] 3. Preparation of Cu-Ti solder
[0116] Use an electronic balance to measure Cu powder and TiH2 powder in a mass ratio of 3:1, and then put the two into a mortar and grind them to obtain a uniform mixed powder solder.
[0117] 4. Assembly of welded parts
[0118] The cleaned ceramic composite material matrix, brazing material, and metal matrix are stacked in order from top to bottom, placed on a stone grinding disc, and then fixed with a pressing block and placed in a vacuum furnace.
[0119] 5. Place the parts to be welded in a vacuum brazing furnace for vacuum brazing to complete the brazing of the ZSC ceramic composite material and the nickel-based high-temperature alloy;
[0120] The vacuum brazing process is as follows: under vacuum conditions, the temperature is raised to 950° C. at a heating rate of 15° C. / min and kept at that temperature for 10 minutes, and then the temperature is lowered to room temperature at a cooling rate of 5° C. / min.
[0121] The shear test was carried out using an electronic universal testing machine with a loading speed of 0.5 mm / min. The room temperature shear strength of the connection joint obtained in Comparative Example 1 was 24 MPa. Figure 4 The element surface scan of the joint shows that due to the strong affinity between Ni and Ti, a large amount of Ni in the GH99 base material dissolves into the brazing filler metal during the brazing process, and combines with Cu and Ti elements in the center of the weld to form a continuous layered Cu-Ti-Ni ternary compound, which increases the brittleness of the joint and has an adverse effect on the strength.
Claims
1. A brazing method for ZrB2-SiC-C ceramic composite material and nickel-based high-temperature alloy, characterized in that: The brazing method of ZrB2-SiC-C ceramic composite material and nickel-based high-temperature alloy is carried out according to the following steps:
1. Grinding and cleaning of ZrB2-SiC-C ceramic composite materials before welding; 2. Grind and clean the nickel-based high-temperature alloy before welding; 3. preparing a Cu-Ti solder; the mass fraction of TiH2 in the Cu-Ti solder is 10%-40%; 4. Grinding and cleaning the Nb foil before welding; the thickness of the Nb foil is 50-200 μm; 5. Assembly of welded parts: stack and fix the ZrB2-SiC-C ceramic composite material, Cu-Ti brazing filler metal, Nb foil, Cu-Ti brazing filler metal, and nickel-based high-temperature alloy in this order to obtain the welded parts; 6. Put the parts to be welded into the vacuum brazing furnace for vacuum brazing. The vacuum brazing process is as follows: under vacuum conditions, heating to 910°C-990°C at a heating rate not exceeding 15°C / min and keeping the temperature for 1-40min, and then cooling to room temperature at a cooling rate of 10°C / min.
2. The brazing method of the ZrB2-SiC-C ceramic composite material and the nickel-based high-temperature alloy according to claim 1, characterized in that: The pre-welding grinding and cleaning treatment method described in step 1 is: the surface to be welded of the ZrB2-SiC-C ceramic composite material is ground step by step, and after grinding, it is placed in a cleaning agent for ultrasonic cleaning for 5-60 minutes; the cleaned ZrB2-SiC-C ceramic composite material is placed in anhydrous ethanol or acetone for liquid sealing for standby use; the cleaning agent is anhydrous ethanol or acetone.
3. The brazing method of the ZrB2-SiC-C ceramic composite material and the nickel-based high-temperature alloy according to claim 1, characterized in that: The pre-welding grinding and cleaning treatment method in step 2 is as follows: grinding the surface to be welded of the nickel-based high-temperature alloy step by step, and then placing it in a cleaning agent for ultrasonic cleaning for 5-60 minutes after grinding; the cleaning agent is anhydrous ethanol or acetone.
4. The brazing method of the ZrB2-SiC-C ceramic composite material and the nickel-based high-temperature alloy according to claim 1, characterized in that: Step 3: The preparation method of the Cu-Ti solder is as follows: weigh Cu powder and TiH2 powder, and then grind them evenly to obtain the Cu-Ti solder.
5. The brazing method of the ZrB2-SiC-C ceramic composite material and the nickel-based high-temperature alloy according to claim 1, characterized in that: The pre-welding grinding and cleaning treatment method described in step 4 is: grinding the two surfaces of the Nb foil step by step, placing it in a cleaning agent for ultrasonic cleaning for 5-60 minutes after grinding, and finally cleaning it with a solvent; the cleaning agent is anhydrous ethanol or acetone; the solvent is anhydrous ethanol or acetone.
6. A brazing method for ZrB2-SiC-C ceramic composite material and nickel-based high-temperature alloy, characterized in that: The brazing method of ZrB2-SiC-C ceramic composite material and nickel-based high-temperature alloy is carried out according to the following steps:
1. Grinding and cleaning of ZrB2-SiC-C ceramic composite materials before welding; 2. Grind and clean the nickel-based high-temperature alloy before welding; 3. preparing a Cu-Ti solder; the mass fraction of TiH2 in the Cu-Ti solder is 10%-40%; 4. Grinding and cleaning the Nb foil and the ZrB2-SiC-C ceramic composite material mesh before welding; the thickness of the Nb foil is 50-200 μm; The preparation method of the ZrB2-SiC-C ceramic composite material net is as follows: the ZrB2-SiC-C ceramic composite material is cut into thin slices with a thickness of 0.2-1 mm by wire cutting, and a hole with a diameter of 0.2-1 mm is processed on the thin slice by a pulse laser to obtain the ZrB2-SiC-C ceramic composite material net; the porosity of the ZrB2-SiC-C ceramic composite material net is 5%-30%; 5. Assembly of welded parts: stack and fix the ZrB2-SiC-C ceramic composite material, Cu-Ti brazing filler metal, ZrB2-SiC-C ceramic composite material mesh, Cu-Ti brazing filler metal, Nb foil, Cu-Ti brazing filler metal, and nickel-based high-temperature alloy in this order to obtain the welded parts; 6. Put the parts to be welded into the vacuum brazing furnace for vacuum brazing. The vacuum brazing process is as follows: under vacuum conditions, heating to 910°C-990°C at a heating rate not exceeding 15°C / min and keeping the temperature for 1-40min, and then cooling to room temperature at a cooling rate not exceeding 10°C / min.
7. The brazing method of the ZrB2-SiC-C ceramic composite material and the nickel-based high-temperature alloy according to claim 6, characterized in that: The pre-welding grinding and cleaning treatment method in step 1 is as follows: the surface to be welded of the ZrB2-SiC-C ceramic composite material is ground step by step, and after grinding, it is placed in a cleaning agent for ultrasonic cleaning for 5-60 minutes; the cleaning agent is anhydrous ethanol or acetone.
8. The brazing method of the ZrB2-SiC-C ceramic composite material and the nickel-based high-temperature alloy according to claim 6, characterized in that: The pre-welding grinding and cleaning treatment method described in step 2 is: grinding the surface to be welded of the nickel-based high-temperature alloy step by step, and placing it in a cleaning agent for ultrasonic cleaning for 5-60 minutes after grinding; the cleaned nickel-based high-temperature alloy is placed in anhydrous ethanol or acetone for liquid sealing for standby use; the cleaning agent is anhydrous ethanol or acetone.
9. The brazing method of the ZrB2-SiC-C ceramic composite material and the nickel-based high-temperature alloy according to claim 6, characterized in that: Step 3: The preparation method of the Cu-Ti solder is as follows: weigh Cu powder and TiH2 powder, and then grind them evenly to obtain the Cu-Ti solder.
10. The brazing method of the ZrB2-SiC-C ceramic composite material and the nickel-based high-temperature alloy according to claim 6, characterized in that: The pre-welding grinding and cleaning treatment method described in step 4 is: grinding the two surfaces of the Nb foil step by step, placing it in a cleaning agent for ultrasonic cleaning for 5-60 minutes after grinding, and finally cleaning it with a solvent; the cleaning agent is anhydrous ethanol or acetone; the solvent is anhydrous ethanol or acetone.
Citation Information
Patent Citations
Flexible composite middle layer brazing alloy and method of utilizing brazing ceramic and metal
CN102699558A
Brazed connection method of C / SiC composite materials
CN105016761A
Braze-welding method for ceramic or ceramic-based composite material and metal through composite interlayer
CN106493443A
Connector based on nickel-based high temperature alloy and ceramic, and preparation method of connector
CN110734296A
Method for assisting brazing of dissimilar materials through bionic structure middle layer
CN117182231A